Rapid assessment procedure for loiasis and mapping lymphatic filariasis: two perfect illustrations of "to be in English or not to be". - Bernard Carme (Public Library of Science (PLoS), 2012)
Interest in filariasis has found a new impetus now that neglected tropical diseases have their own journal. However, some of the advances published in renowned international journals have completely ignored previous publications on the subject, particularly those in languages other than English. The rapid assessment procedure for loiasis and the mapping of lymphatic filariasis provide two perfect illustrations of this. This problem may seem a bit outdated, given that all "good authors" now publish exclusively in English. It certainly is outdated for most areas of medicine. But, surely, this should not be the case for neglected tropical diseases, for which certain long-standing findings are every bit as important as what may be presented as new discoveries. One possibility would be for certain journals, such as PLOS Neglected Tropical Diseases, to include a specific heading permitting the publication in English of older studies that initially appeared in a language other than English. The texts would be English versions respecting the entirety of the original text. Submission should be accompanied by a presentation of the problem, with details and explanatory comments, with submission at the initiative of the authors of the former article in question or their students or sympathizers.